Evaluation of Light-Dependent Photosynthetic Reactions in Reynoutria japonica Houtt. Leaves Grown at Different Light Conditions - Mlinarić, Selma; Begović, Lidija; Tripić, Neven; Piškor, Antonija; Cesar, Vera (Frontiers in Plant Science, 2021)
Japanese knotweed (Reynoutria japonica Houtt.) is considered as one of the most aggressive and highly successful invasive plant with negative impact on invaded habitats. Its uncontrolled expansion became significant threat to native species throughout Europe. Due to its extensive rhizome system, rapid growth and allelopatic activity it usually forms monocultures that negatively affect nearby vegetation. Efficient regulation of energy partitioning and utilisation in photosynthesis enables invasive plants to adapt rapidly in a variety of environmental conditions. Therefore, we aimed to determine the influence of light conditions on photosynthetic reactions in Japanese knotweed. Plants were grown under two different light regimes: constant low (CLL, 40 mol m-2s-1) and fluctuating light (FL, 0-1250 mol m-2s-1). To evaluate photosynthetic performance, direct and modulated chlorophyll a fluorescence was measured. Plants grown at constant low light served as control. Photosynthetic measurements revealed better photosystem II (PSII) stability and functional oxygen evolving centre of plants grown at fluctuating light. They also exhibited more efficient conversion of excitation energy to electron transport and efficient electron transport beyond primary electron acceptor QA, all the way to the PSI. Enhanced photochemical activity of PSI suggested formation of successful adaptive mechanism by regulating the distribution of excitation energy between PSII and PSI to minimize photooxidative damage. Faster oxidation at PSI side most probably resulted in generation of the cyclic electron flow around PSI. In addition, short term exposure of FL grown knotweeds to high light intensity increased the yield induced by downregulatory processes suggested that generation of the cyclic electron flow served as a protection of PSI from photoinhibition.